Ethnic predisposition of diabetes mellitus in the patients with previous history of gestational diabetes mellitus: A review - Gupta, Rajat Das; Gupta, Sabyasachi; Das, Anupom; Biswas, Tuhin; Haider, Mohammad Rifat; Sarker, Malabika (Tayor & Francis Online, 2022)
This article was published in the Expert Review of Endocrinology & Metabolism [© Published by Taylor and Francis ] and the definite version is available at : https://doi.org/10.1080/17446651.2018.1471354 The Journal's website is at: https://www.tandfonline.com/doi/full/10.1080/17446651.2018.1471354?needAccess=true